Respon Masyarakat Terhadap Komunikasi Mahasiswa KKN di Desa Londut Kecamatan Kualuh Hulu - Nurul Saniah; Firdayanti Firdaus (Departement of Mathematics Education, 2023)
One form of the Tridarma of higher education is community service. Which aims to establish relationships with the community, train students to communicate and apply the scientific fields acquired while being student, and add insight and experience to student in increasing awareness of the community. The purpose of this study was to determine the community’s response to KKN student communication in Londut Village, Kualuh Hulu District. Student communication with the community greatly impact the KKN activities carried out by student. There are many student KKN activities that can be utilized by community. Between student and the community must communicate wall, so there is ni miss communication. The methods used in this study werw interviews and direct observation of several Londut community leaders, Kualuh Hulu District. They also directly communicate with KKN student. The importance of this research is that before student carry out KKN activities in their respective place they must be able to communicate wall. And prepare matters related to the theme of KKN activities with their respective scientific fields.